1994
DOI: 10.1177/027112149401400205
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Outcomes of Young Children Prenatally Exposed to Illicit Drugs

Abstract: The purpose of this article was to review the findings from existing peer-reviewed experimental studies describing the behavioral and developmental outcomes associated with prenatal exposure to illicit drugs. Forty-six such studies and 460 individual outcomes occurring from birth to 60 months were identified. Only half of these outcomes (49.8%) were statistically significant, indicating adverse effects of prenatal exposure. The greatest number of outcomes were identified for infants younger than 1 month of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In contrasting drug-exposed children and nonexposed children of comparable socioeconomic status (SES), the former have shown more problems in specific neurological or cognitive domains (Mayes & Bornstein, 1997), but on psychological dimensions, group difference tend to be negligible. Summarizing the results of 46 studies on behavioral outcomes of young children prenatally exposed to drugs, Carta et al (1994) reported significant effects for only half the outcomes examined, and the majority of these were among infants less than 1 month old, and were chiefly in the neurodevelopmental domain.…”
Section: Maternal Drug Abuse and Other Psychopathology: Disentanglingmentioning
confidence: 99%
“…In contrasting drug-exposed children and nonexposed children of comparable socioeconomic status (SES), the former have shown more problems in specific neurological or cognitive domains (Mayes & Bornstein, 1997), but on psychological dimensions, group difference tend to be negligible. Summarizing the results of 46 studies on behavioral outcomes of young children prenatally exposed to drugs, Carta et al (1994) reported significant effects for only half the outcomes examined, and the majority of these were among infants less than 1 month old, and were chiefly in the neurodevelopmental domain.…”
Section: Maternal Drug Abuse and Other Psychopathology: Disentanglingmentioning
confidence: 99%
“…Challenging behaviors present the single biggest obstacle to including young children with disabilities in typical early education programs (Conroy, Dunlap, Clarke, & Alter, 2005). If challenging behaviors are not reduced and replaced with more appropriate behavior, students who display them are likely to be removed from an inclusive class and placed in a more restrictive environment (Carta et al, 1994;Palfrey, Singer, Walker, & Butler, 1987).…”
Section: Promoting Inclusion and Peer Participationmentioning
confidence: 99%
“…Without effective early services for children with challenging behaviors, the prognosis is disheartening. Untreated challenging behaviors result in the need for more costly intervention and treatments, such as more restrictive placements, and an increased likelihood of requiring special education services later in life (Carta et al, 1994; Dodge, 1993; Palfrey, Singer, Walker, & Butler, 1987; Reid, 1993).…”
mentioning
confidence: 99%